Ochratoxicosis in poultry: occurrence, environmental factors, pathological alterations and amelioration strategies. Issue 3 (3rd July 2022) - Tahir, Muhammad A.; Abbas, Asghar; Muneeb, Muhammad; Bilal, Rana M.; Hussain, Kashif; Abdel-Moneim, Abdel-Moneim E.; Farag, Mayada R.; Dhama, Kuldeep; Elnesr, Shaaban S.; Alagawany, Mahmoud
SUMMARY: Mycotoxins are secondary metabolites, and some important groups of mycotoxins are aflatoxins, ochratoxins, ergot alkaloids, citrinin, patulin and fusarium, which include trichothecenes, fumonisins and zearalenone. Ochratoxins are one of the most lethal mycotoxins; specifically, Ochratoxins A (OTA), which is perilous to the productivity and wellbeing of poultry birds. Ochratoxin species tend to grow in warmer climates such as Aspergillus ochraceous as well as colder climates such as Penicillium verrucosum . It has been known to cause toxicity in broilers and layers more as compared to aflatoxins. Its toxicological profile designates it as carcinogenic, nephrotoxic, teratogenic, immunotoxic and mutagenic. It is also a potential hazard for human health when animal-derived commodities are consumed. The presence of ochratoxins within poultry feed has undesirable influences on the growth and quality of the final product in the form of eggs and meat. Moreover, ochratoxins cause economic losses by affecting productive performance and lead to histopathological changes in the organs of birds, negatively affecting the bird's health. Some agents such as vitamins E and C, silymarin, activated charcoal, distillery yeast sludge and indigenous mycotoxin binders were used to reduce the effects of OTA toxicity on poultry. This review comprehensively explains the ochratoxins, the environmental factors responsible for their occurrence and their persistence as a major threat to poultry production as well as potential ameliorative strategies.